I assume your solving for "x," correct?
2(3x - 4) - 7 = 3x + 1 + x
First: eliminate parenthesis --- distribute the outer term with the terms in parenthesis....
2(3x) + 2(- 4) - 7 = 3x + 1 + x
6x + (-8) - 7 = 3x + 1 + x
6x - 8 - 7 = 3x + 1 + x
*Combine "like" terms on both sides....
6x - 15 = 4x + 1
Sec: add "15" with both sides (when you move a term to the opposite side, alwayse use the opposite sign)....
6x - 15 + 15 = 4x + 1 + 15
6x = 4x + 1 + 15
6x = 4x + 16
*Subtract "4x" from both sides....
6x - 4x = 4x - 4x + 16
6x - 4x = 16
2x = 16
Third: isolate "x" on one side --- divide both terms by "2"....
2x/2 = 16/2
x = 16/2
x = 8
2007-02-13 01:08:23
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
0⤊
1⤋
2(3x-4)-7=3x+1+x
First multiply out the brackets, this equals to
6x-8-7=3x+1+x
6x-15=4x+1 Add 15 to both sides
6x-15+15=4x+1+15
6x=4x+16 Subtract 4x from both sides
6x-4x=16+4 x-4x
2x=16
Therefore
x=8
2007-02-13 01:04:03
·
answer #2
·
answered by The exclamation mark 6
·
0⤊
0⤋
I can't be so complicated! first multiply 2 in ( 3x - 4 ). the result is (6x - 8 ) next you will have : 6x - 8 - 7 that = 6x - 15 . on the other hand you simply have 3x + 1 + x that = 4x + 1
so the question is 6x - 15 = 4x + 1
again simply by changing the sides : 2x = 16 and X = 8 !
correct!??
2007-02-13 01:31:31
·
answer #3
·
answered by Soren 2
·
0⤊
0⤋
2 (3x - 4) - 7 = 3x +1 + x
6x -8 - 7 = 4x + 1
6x -15 = 4x + 1
2x - 15 = 1
2x = 16
x = 8
2007-02-13 01:01:51
·
answer #4
·
answered by Doctor Q 6
·
0⤊
0⤋
2(3x - 4) - 7 = 3x + 1 + x
6x - 8 - 7 = 4x + 1
6x - 15 = 4x + 1
6x - 15 - 4x = 4x + 1 - 4x
2x - 15 = 1
2x - 15 + 15 = 1 + 15
2x = 16
2x/2 = 16/2
x = 8
- - - - - - - -s-
2007-02-13 03:02:10
·
answer #5
·
answered by SAMUEL D 7
·
0⤊
0⤋
2(3x-4)-7=3x+1+x
6x-8-7=4x+1 (consolidate the variables)
6x-15=4x+1 (add -8 and -7 on the left to consolidate)
2x-15=1 (subtract 4x from each side)
2x=16 (add 15 to each side)
x=8 (divide each side by 2)
2007-02-13 01:04:44
·
answer #6
·
answered by Matthew P 4
·
0⤊
0⤋
2(3x-4)-7=3x+1+x
6x-8-7=4x+1
6x -15 = 4x +1
-4x +15 -4x +15
-----------------------
2x=16
x=8
2007-02-13 01:08:10
·
answer #7
·
answered by Tyler M 2
·
0⤊
0⤋
(6x-8)-7= 4x+1 bcuz: 3x+x=4x
6x-15=4x+1 bcuz: -8-7= -8+-7= -15
-15=4x-6x+1 bcuz: subtract 6x
-15=-2x+1
-15-1=2x
-16=2x
-16/2=2x/2
-8=x
hope this helps!!!! :)
2007-02-13 01:08:57
·
answer #8
·
answered by katsrkutesz11 2
·
0⤊
0⤋
2(3x-4)-7=3x+1+x
6x-8-7=4x+1
6x-15=4x+1
6x-4x=1+15
2x=16
x=8
2007-02-13 01:01:42
·
answer #9
·
answered by Xiomy 6
·
0⤊
0⤋
6x-8-7=4x+1
6x-15=4x+1
6x-4x=1+15
2x=16
x=8
2007-02-13 02:32:10
·
answer #10
·
answered by Akshav 3
·
0⤊
0⤋